2020
DOI: 10.5578/turkjsurg.4547
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of clinical pathway in gastric cancer surgery

Abstract: Objective: Clinical pathways are useful tools for surgical quality improvement and better peri-operative clinical outcomes for patients undergoing major surgery. This study aimed to evaluate the influence of clinical pathway on early postoperative outcomes for gastric cancer patients. Material and Methods: The study was designed as a retrospective cohort observational study. Patients who had undergone curative gastrectomy for gastric cancer were evaluated by using the gastric cancer database, which was prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Sixteen studies met the inclusion criteria for studies of pathway interventions (Table 5). Most studies were conducted in the United States, 30,31,34,49-52,54,55 and others were conducted in Turkey, 53,58 South Korea, 56 Germany, 57 Belgium, 28 and China. 27,59 Disease sites included breast, 28,49-52,57,58 colorectal, 55 lung, 27,30,31 gastric, 53,56 a combination of disease sites, 54 or patients with bone metastases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen studies met the inclusion criteria for studies of pathway interventions (Table 5). Most studies were conducted in the United States, 30,31,34,49-52,54,55 and others were conducted in Turkey, 53,58 South Korea, 56 Germany, 57 Belgium, 28 and China. 27,59 Disease sites included breast, 28,49-52,57,58 colorectal, 55 lung, 27,30,31 gastric, 53,56 a combination of disease sites, 54 or patients with bone metastases.…”
Section: Resultsmentioning
confidence: 99%
“…49 All studies were observational studies conducted without random assignment of patients to treatment or control groups. All studies were either a comparison of groups before versus after implementation of a pathway 27,28,30,34,49,50,53,54,57,58 or contemporaneous studies of patients who were on pathway versus off pathway. 31,51,52,55,56 Balance of study characteristics between intervention and control groups is reported in Table 5; some studies used statistical techniques such as propensity score matching to ensure that groups were balanced on characteristics such as age, stage, and extent of comorbidities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations